2021
DOI: 10.1002/prot.26273
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial membrane protein Large 3‐like‐family proteins in bacteria, protozoa, fungi, plants, and animals: A bioinformatics and structural investigation

Abstract: Lipid transporters play an important role in most if not all organisms, ranging from bacteria to humans. For example, in Mycobacterium tuberculosis, the trehalose monomycolate transporter MmpL3 is involved in cell wall biosynthesis, while in humans, cholesterol transporters are involved in normal cell function as well as in disease.Here, using structural and bioinformatics information, we propose that there are proteins that also contain "MmpL3-like" (MMPL) transmembrane (TM) domains in many protozoa, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In the mycobacteria, SQ109 is thought to target primarily the trehalose monomycolate transporter MmpL3 in addition to acting as a protonophore uncoupler [12]. Although there is an MmpL3-like protein in T. cruzi [34], its function is not known, and MmpL3 proteins are not present in T. brucei, L. donovani or in humans. The most likely reason for the strong correlation between the activity of SQ109 and the activity of the mono-oxygenated metabolites is, therefore, likely to be due to a more "physical" effect, for example, differences in cell membrane solubility between the metabolites, leading to differences in uncoupling activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the mycobacteria, SQ109 is thought to target primarily the trehalose monomycolate transporter MmpL3 in addition to acting as a protonophore uncoupler [12]. Although there is an MmpL3-like protein in T. cruzi [34], its function is not known, and MmpL3 proteins are not present in T. brucei, L. donovani or in humans. The most likely reason for the strong correlation between the activity of SQ109 and the activity of the mono-oxygenated metabolites is, therefore, likely to be due to a more "physical" effect, for example, differences in cell membrane solubility between the metabolites, leading to differences in uncoupling activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies aiming to search for compounds with antifungal action found activity of the compound MMV687273 (SQ109) against Candida albicans biofilms 33 and Aspergillus fumigatus . 57 SQ109, in addition to exhibiting antibacterial activity against M. tuberculosis , 58 is also active against Trypanosoma cruzi 59 and was recently proposed as a new drug for the treatment of Chagas disease, 59 , 60 strongly suggesting its potential use for the treatment of different infectious diseases. This compound inhibits the trehalose monomycolate transporter MmpL3 in M. tuberculosis , which has homology with sphingolipid transporters found in fungi, 57 suggesting a mechanism of action for this compound distinct to that presented by currently used antifungal drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale to prepare and test the triazole analogs of JS-2-02 against T. gondii and C. parvum stems from the fact that the small molecule SQ109, which was originally reported as an effective inhibitor of mycobacterial MmpL3 ( Tahlan et al, 2012 ) and is currently being investigated in clinical trials for tuberculosis, has shown potent efficacy against protozoan parasites including T. gondii ( Li et al, 2015 ; Baek et al, 2022 ). While bona fide MmpL3 transporter has not been identified in T. gondii or C. parvum , MmpL3-like proteins have been proposed to be present in many protozoa among other living organisms ( Malwal et al, 2021 ; Malwal and Oldfield, 2022 ).…”
Section: Introductionmentioning
confidence: 99%